CONSTRAINTS TO THE PROTECTION OF COMMUNAL INTELLECTUAL PROPERTY THROUGH INVENTORY BY THE DIRECTORATE GENERAL OF INTELLECTUAL PROPERTY - M. Citra Ramadhan; Fitri Yanni Dewi Siregar (Kanun Jurnal Ilmu Hukum, 2022)
This purpose of this research is to identify the constrains that arise in the inventory efforts carried out by the Directorate General of Intellectual Property at the Ministry of Law and Human Rights of the Republic of Indonesia in order to realize the legal protection of communal intellectual property. The method used is normative legal research with an evaluative nature, where the sources of legal material obtained in this research are then analyzed qualitatively. The constrains that have been identified are: Constraints in terms of substance, related to the confusion of communal intellectual property rights holders; Constraints in terms of structure, related to coordinating the inventory of communal intellectual property without involving a custodian; Constraints in terms of culture, related to the culture of speech for the custodian of communal intellectual property in Indonesia. These constrains will certainly hinder the government’s efforts to realize the legal protection of Indonesian communal intellectual property. Therefore, it is necessary to make improvements from several aspects, namely: First, the holder of communal intellectual property rights is the custodian; Second, the inventory should be carried out directly or at least involve the custodian; Third, grounding the documentation culture in communal intellectual property custodians in Indonesia